Investigating the motivations and constraints of Chinese peer-to-peer accommodation hosts. Issue 1 (10th December 2020) - Li, ShiNa; Fong, Lawrence Hoc Nang; Zhang, Carol Xiaoyue; Chen, Mengxin
Abstract : Purpose: This paper aims to identify peer-to-peer accommodation hosts' perceived motivations and constraints, to examine the prediction of the motivation and constraint factors on hosts' intention to continue business based on hosts' attitudes and to explore the moderating role of the business scale. Design/methodology/approach: A scale for hosts' perceived motivators and constraints was developed. Mixed methods were used to develop and analyse a conceptual framework for demonstrating how constraints and motivations influence hosts' behavioural intentions. Findings from interviews with hosts interpretatively supported the survey results. Findings: Chinese hosts' perceived constraints and motivators are identified and explained. The survey results indicate that constraints lower intention to continue one's business and motivators heightens it. Motivators have a higher effect on attitudes and intentions than constraints do. The business scale was confirmed as a moderator in the constraint–attitude link but not in the motivator–attitude relationship. Practical implications: This paper offers policy implications for governments, online platforms and hosts in terms of establishing incentives and solving problems so that Chinese hosts can sustainably operate their businesses. Originality/value: This paper identifies constraints and motivators and develops a measurement scale for both simultaneously, which provides a holistic explanation of hosts' attitude and behavioural intention. It also reveals the moderating role of the business scale. In investigating the thoughts of existing hosts operating on global and local platforms in China, this paper complements the literature, which mainly focuses on the Western context and a single global platform.